2012
DOI: 10.1590/s1517-83822012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of periodontal pathogens among patients with chronic periodontitis

Abstract: The aim of the present study was to evaluate the presence of the periodontal pathogens that form the red complex (Tannerella forsythia, Porphyromonas gingivalis and Treponema denticola) and Aggregatibacter actinomycetemcomitans in patients with chronic periodontitis. The sample consisted of 29 patients with a clinical and radiographic diagnosis of chronic periodontitis based on the criteria of the American Academy of Periodontology (3). Samples for microbiological analysis were collected from the four sites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
2
18
2
5
Order By: Relevance
“…Also, Pd patients harbored higher proportion and/or counts than CG of the following bacteria: A. gerencseriae, S. sanguinis, C. sputigena, P. gingivalis, T. denticola, and T. socranskii. However, we observed that both healthy and diseased sites of Pd patients presented similar prevalence and counts of bacteria, contradicting findings of a former study which showed that levels of red complex bacteria seem to be related to Periodontitis severity 18 . It is important to note that this study only assessed deep sites 18 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Also, Pd patients harbored higher proportion and/or counts than CG of the following bacteria: A. gerencseriae, S. sanguinis, C. sputigena, P. gingivalis, T. denticola, and T. socranskii. However, we observed that both healthy and diseased sites of Pd patients presented similar prevalence and counts of bacteria, contradicting findings of a former study which showed that levels of red complex bacteria seem to be related to Periodontitis severity 18 . It is important to note that this study only assessed deep sites 18 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, we observed that both healthy and diseased sites of Pd patients presented similar prevalence and counts of bacteria, contradicting findings of a former study which showed that levels of red complex bacteria seem to be related to Periodontitis severity 18 . It is important to note that this study only assessed deep sites 18 . Furthermore, Red complex can be detected in both supra-and subgingival samples as well as in healthy and diseased sites from periodontitis patients 7,8 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study focused on adult Brazilians demonstrated the significant prevalence of P. gingivalis in deep pockets, but also of T. forsythia (Farias et al, 2012). The fact that we identified T. denticola as bearing the strongest correlation with maximum probing depth could be representing a local trait, as several studies indicated that periodontal pathogens' distribution and prevalence vary with geographic location (Tettamanti et al, 2017) and ethnicity (Gatto et al, 2014).…”
Section: Actinomycetemcomitanssupporting
confidence: 48%
“…Further, more needs to be done to identify the risk factors involved in disease progression, and how best to prevent disease progression. As practitioners target more precise therapies, it is important to realize that Pg, Td, and Tf are strongly associated with disease progression as documented by our findings and many others (Farias et al, 2012;Nomura et al, 2017;Teles et al, 2008); thus, these periodontal pathogens should be targeted for elimination, if progression of periodontitis is to be halted.…”
Section: Discussionmentioning
confidence: 73%